Copy Number Variation and Structural Genomic Findings in 116 Cases of Sudden Unexplained Death between 1 and 28 Months of Age. Issue 1 (7th November 2022) - Brownstein, Catherine A.; Douard, Elise; Haynes, Robin L.; Koh, Hyun Yong; Haghighi, Alireza; Keywan, Christine; Martin, Bree; Alexandrescu, Sanda; Haas, Elisabeth A.; Vargas, Sara O.; Wojcik, Monica H.; Jacquemont, Sébastien; et al.
Abstract: In sudden unexplained death in pediatrics (SUDP) the cause of death is unknown despite an autopsy and investigation. The role of copy number variations (CNVs) in SUDP has not been well‐studied. Chromosomal microarray (CMA) data are generated for 116 SUDP cases with age at death between 1 and 28 months. CNVs are classified using the American College of Medical Genetics and Genomics guidelines and CNVs in our cohort are compared to an autism spectrum disorder (ASD) cohort, and to a control cohort. Pathogenic CNVs are identified in 5 of 116 cases (4.3%). Variants of uncertain significance (VUS) favoring pathogenic CNVs are identified in 9 cases (7.8%). Several CNVs are associated with neurodevelopmental phenotypes including seizures, ASD, developmental delay, and schizophrenia. The structural variant 47, XXY is identified in two cases (2/69 boys, 2.9%) not previously diagnosed with Klinefelter syndrome. Pathogenicity scores for deletions are significantly elevated in the SUDP cohort versus controls ( p = 0.007) and are not significantly different from the ASD cohort. The finding of pathogenic or VUS favoring pathogenic CNVs, or structural variants, in 12.1% of cases, combined with the observation of higher pathogenicity scores for deletions in SUDP versus controls, suggests that CMA should be included in the genetic evaluation of SUDP. Abstract : Chromosomal microarray (CMA) data for 116 sudden unexplained death in pediatrics (SUDP) cases is compared to an autism spectrum disorder (ASD) cohort and a control cohort. Pathogenicity scores for deletions are significantly elevated in the SUDP cohort versus controls ( p = 0.007) and are not significantly different from the ASD cohort. This data suggests that CMA should be included when evaluating SUDP.